Respons tanaman tebu (Saccharum officinarum L.) terhadap aplikasi konsorsium biostimulan di tiga tipologi lahan - Ciptadi Achmad YUSUP; Deddy PURWANTORO; Happy WIDIASTUTI; . SISWANTO; Djoko SANTOSO; . PRIYONO (Menara Perkebunan, 2021)
The consortium biostimulant combines several types of biostimulant applied holistically, such as phytohormones to induce physiological processes, humic acid to improve nutrition intake and land fertility, and biofertilizer arbuscular mycorrhizal fungi to improve abiotic stress tolerance. The objectives of this research were to analyze the effect of application consortium biostimulant on the growth and productivity of Bululawang sugarcane variety planted in three land typologies, i.e. irrigated heavy soil with good drainage (BPL), irrigated heavy soil with poor drainage (BPJ), and rainfed light soil with good drainage (RHL). The research was conducted on plant cane (PC) sugarcane areal in Lumajang Regency, East Java, from July 2019 to September 2020. The treatment plot area was 1 ha for each land typologies, and the observation were conducted on 10 m plant row with ten times replications. Each treatment was replicated ten times. The results showed that the application of consortium biostimulant could induce faster growth of sugarcane shoots and better roots at one month after planting (MAP). Stalk height and diameter showed significantly different values between treatment and control at the plant age 6 to 12 MAP. In addition, the sugarcane stalk weight per meter row also increases by 13.72 – 28.57%. The growth performance of sugarcane on a commercial scale increased, also sugarcane productivity increased by 11.08 – 20.36%. The potential sugar yield increased by 15.05% in BPL land typology, 4.9% in BPJ land typology, and 9.7% in RHL land typology. The difference in land typologies affected the effectiveness of the consortium biostimulant application in increasing sugarcane productivity.